Two-hour nasal responses after a single dose of ephedrine nasal spray in healthy males - Cheewin Trakarnsilpa (2018)
© 2017, Medical Association of Thailand. All rights reserved. Background: Ephedrine is often used as nasal decongestant. Yet, the clinical study of intranasal ephedrine is scarce. In addition, the study tools may affect the measurement of the nasal patency. This problem has not been concerned. Objective: To investigate the nasal responses after using a single-dose of calibrated ephedrine nasal spray in Thai healthy male volunteers. The study also compared the differences between two methods of nasal patency measurement. Material and Method: Healthy males (n = 20) were recruited in a randomized, crossover, 2-day study. Each day was studied for anterior rhinomanometry (RN) or peak nasal inspiratory flow (PNIF). On test day, subjects were given ephedrine nasal spray, and measured by the specific tool for two hours. In addition, the visual analogue scale (VAS), cardiovascular (CVS) parameters, and adverse drug reactions were examined. Results: A single-dose ephedrine nasal spray significantly changed the nasal airway resistance (NAR), PNIF, and VAS at 5-minute. The NAR via RN was maximally decreased by 43.74±16.3% at 10-minute and returned to baseline at 90-minute. While, PNIF was maximally increased by 31.20±18.4% at 10-minute and returned to baseline at 60-minute. The nasal responses measured by two methods were significantly different at 5-, 15-, and 45-minute. VAS for nasal patency showed significant increases throughout the study period. CVS effects were negligible. Bitter taste was the most common adverse event reported. Conclusion: Ephedrine nasal spray is a fast-onset, short-acting decongestant. The decongestant effect of the drug varied by study tools. The variations appeared on the degree of nasal response and duration of action. The drug was generally safe.